Pengenalan Kepribadian Seseorang Melalui Bentuk Tulisan Tangan Menggunakan Metode Radial Basis Function Neural Network (RBFNN) - Magfiroh, Alfin (Universitas Islam Madura, 2022)
Humans are created with a variety of different characters and characters, so that the personality that is formed is very diverse according to the character and character of each person. With a variety of personalities, it appears that there are differences in quality and quantity between humans from one another in the view of society. There are various ways to get to know a person's personality, one of which is through handwriting with specific letters of the alphabet. In this study, handwriting is limited to the letter 't' only and has been generated from 26 images of 't' training which were previously processed using the PCA method, there are 10 images according to the type 't' 1 and 16 images according to the type 't ' 2nd and no image matches the 3rd 't' type.